Unsur Postkolonial dalam Novel Atheis Karya Achdiat K. Mihardja - Yunita, Vivi; Asri, Yasnur; Afnita, Afnita (Universitas Negeri Padang, 2012)
The purpose of this study was to describe postcolonial component which was hegemony and mimicry that was experienced by characters in Atheis novel from Achdiat K. Mihardja. Data of study were characters utterance, display of narrator and acting of the characters in the novel. The primary source of data was texts from Atheis novel by Achdiat K. Mihardja. Data were collected by using qualitative decriptive which was read and written into inventaritation data from and analyzing data based on postcolonial theory. The fiding of the study showed postcolonial component in the novel, they were hegemony and mimicry. Five ideologies that were showed hegemony, languange mimicry and culture that was exeperienced by the characters in Atheis novel from Achdiat K. Mihardja.